PHYTODEPURATION PROCESS FOR THE RECYCLING OF WASTEWATER IN DAIRY - Ferrara, Lydia (European Scientific Journal, ESJ, 2013)
The problem of saving water is very important for the need to rationalize the use of the water resource. We have tested a method founded on phytodepuration for waste water of cheese factory, for to recover and recycle the water used in food industry, a sector characterized by high consumption of water . The phytodepuration represents an innovative method for the disposal of wastewater. Some plants have a natural capacity to absorb and / or degrade toxic substances and contaminants to the environment, for the presence of a rhizosphere microflore, which is able to metabolize and make them available for their growth. In the laboratory we developed a little system for phytodepuration using a plastic basin in which were placed some plants of Cyperus papirus immersed in a quantity of wastewater remained constant over time. We performed the analysis before the process and then a distance a few months to verify the variation of the parameters most important pollutants. At the end of our experience, approximately one year, it was possible to draw the following conclusions: the Cyperus papyrus proved effective to lessen the concentration of organic substances: the value of COD was lower than the initial wastewater; the concentration of phosphorus, of zinc was decreased and the concentration of chlorides also, which remained constant until the end of the experience.The plants after the stage of adjustment is not showing signs of suffering and therefore can be considered suitable for such use.